Dynamic and Differential Expression of Duplicated Cxcr4/Cxcl12 Genes Facilitates Antiviral Response in Hexaploid Gibel Carp - Lu, Wei-Jia; Zhou, Li; Gao, Fan-Xiang; Zhou, Yu-Lin; Li, Zhi; Zhang, Xiao-Juan; Wang, Yang; Gui, Jian-Fang (Frontiers in Immunology, 2020)
Chemokine receptor cxcr4 and its ligand cxcl12 have evolved two paralogs in the teleost lineage. In this study, we have identified four duplicated cxcr4 and cxcl12 genes from hexaploid gibel carp, Carassius gibelio, respectively. Cgcxcr4bs and Cgcxcl12as were dynamically and differentially expressed in immune-related tissues, and significantly up-regulated in head kidney and spleen after crucian carp herpesvirus (CaHV) infection. Blocking Cxcr4/Cxcl12 axis by injecting AMD3100 brought more severe bleeding symptom and lower survival rate in CaHV-infected fish. AMD3100 treatment also suppressed the up-regulation of key antiviral genes in head kidney and spleen, and resulted in more acute replication of CaHV in vivo. Consistently, the similar suppression of up-regulated expression of key antiviral genes were also observed in CAB cells treated by AMD3100 after poly(I:C) stimulation. Finally, MAPK3 and JAK/STAT were identified as the possible pathways that CgCxcr4s and CgCxcl12s participate in to promote the antiviral response in vitro.